2022
DOI: 10.17305/bjbms.2022.7930
|View full text |Cite
|
Sign up to set email alerts
|

Promotive role of USP29-mediated deubiquitination in malignant proliferation of colorectal cancer cells via the KIAA1429/SOX8 axis

Abstract: Colorectal cancer (CRC) is regarded as one of the most prevalent neoplasms worldwide, and ubiquitination and N6-methyladenosine (m6A) modification regulate the outgrowth of multiple cancers. This study attempted to explore the effect of ubiquitin-specific peptidases 29 (USP29) on the malignant proliferation of CRC cells via stabilizing Vir-like m6A methyltransferase associated (VIRMA/KIAA1429). First, upregulations of USP29, KIAA1429, and SRY-box transcription factor 8 (SOX8) were found in CRC tissues and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“… 22 , 24 , 25 In this study, we revealed the key role of USP29 in promoting nucleotide biosynthesis, given that USP29 may be an alternative target for targeting cancer cell nucleotide metabolism. Indeed, USP29 depletion has been reported to suppress malignant phenotypes in several other cancers, including gastric cancer, 15 , 16 colorectal cancer 14 , 26 and hepatocellular carcinoma cells. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 , 24 , 25 In this study, we revealed the key role of USP29 in promoting nucleotide biosynthesis, given that USP29 may be an alternative target for targeting cancer cell nucleotide metabolism. Indeed, USP29 depletion has been reported to suppress malignant phenotypes in several other cancers, including gastric cancer, 15 , 16 colorectal cancer 14 , 26 and hepatocellular carcinoma cells. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 9 Consistently, USP29 was also reported to sustain glycolysis and sorafenib resistance in hepatocellular carcinoma by stabilizing HIF1α, indicating the important role of USP29 in regulating tumor cell metabolic reprogramming in various types of cancer. 10 Moreover, USP29 was reported to stabilize p53, 11 Claspin, 12 Cdc25A, 13 VIRMA 14 and Snail1 15 , 16 in tumor cells. However, the potential role of USP29 in regulating nucleotide metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…USP29 was highly upregulated in colon cancer tissues and promoted cancer cell proliferation; although the detailed mechanism was unclear, USP29 depletion was reported to delay cell cycle progression 17 . Recently, another study for colon cancer presented the accordant result that USP29 facilitates the malignant proliferation of cancer cells by upregulating the KIAA1429/SOX8 axis both in vitro and in vivo 30 . In our unpublished data, we revealed that USP29 was upregulated in gastric cancers and promoted cell proliferation by forming a FUBP1‐USP29‐AURKB regulatory axis; importantly, deletion of Usp29 in mice markedly suppressed the gastric carcinogenesis induced by benzo[a]pyrene treatment.…”
Section: Usp29 In Cancermentioning
confidence: 99%
“…Knockdown of LINRIS resulted in a decreased level of IGF2BP2 through ubiquitination of IGF2BP2 and attenuated MYC-mediated glycolysis in CRC cells [116] Hsa_circ_0026134 IGF2BP3 HCC Hsa_circ_0026134 expression promoted TRIM25-and IGF2BP3-mediated proliferation and invasion through sponging miR-127-5p [117] miR503HG HNRNPA2B1 HCC Decreased miR503HG exists in HCC. Enhanced expression of miR503HG inhibit HCC invasion and metastasis.miR503HG interact with HNRNPA2B1 and promoted its degradation via the ubiquitin-proteasome pathway, which reduced the stability of p52 and p65 mRNA, and simultaneously suppressed the NF-κB signaling pathway in HCC cells [118] Table 2 (continued) mRNA and protein levels through m 6 A modification to facilitate malignant proliferation in colorectal carcinoma (CRC) [95]. In addition, METTL3 expression has been shown to significantly increase with tumor progression and positively correlate with peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (PIN1) expression in breast cancer tissues.…”
Section: Ubiquitination/deubiquitination Of Writersmentioning
confidence: 99%